Effects of Resistance Training in Individuals with Lower Limb Amputation: A Systematic Review - Miguel L. V. V. Rosario; Pablo B. Costa; Anderson L. B. da Silveira; Kairos R. C. Florentino; Gustavo Casimiro-Lopes; Ricardo A. Pimenta; Ingrid Dias; Claudio Melibeu Bentes (Journal of Functional Morphology and Kinesiology, 2023)
Individuals with lower-limb amputations may have a significant strength deficit. This deficit may be related to the stump length and can lead to changes in gait, reduced energy efficiency, walking resistance, altered joint load, and increased risk of osteoarthritis and chronic low back pain. This systematic review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guidelines to examine the effects of resistance training in lower limb amputees. Interventions with resistance training and other training methods were sufficient to achieve muscle strength gain in muscles of the lower limbs, improved balance, and improvements in gait pattern and speed when walking. However, it was impossible to determine from the results whether resistance training was mainly responsible for these benefits or even whether the positive effects presented would be observed with only this training method. When combined with other exercises, interventions with resistance training made possible gains for this population. Accordingly, it is noteworthy that the main finding of this systematic review is that the effects may be different according to the level of amputation, with mainly transtibial and transfemoral amputations studied.